American Greetings : an automation versus outsourcing dilemma - Nagy, Andrea R., (SAGE knowledge. Cases., 2016)
As part of an industry with generous profit margins and high barriers to entry, American Greetings had spent decades in a comfortable position. Beginning at the turn of the 20th century, it had helped to create a mass market for the greeting card and had presided over its growth into a multi-billion-dollar industry. This case examines the challenges facing American Greetings in the 21st century.